2002
DOI: 10.1002/humu.9054
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype studies of six novelLPL mutations in Chinese patients with hypertriglyceridemia

Abstract: We screened 160 unrelated Chinese hypertriglyceridemic subjects for sequence alterations in the promoter and the 10 exons of the lipoprotein lipase (LPL) gene. We identified one reported mutation (L252R), one common polymorphism (S447X), and six novel mutations: V181I, C283Y, S298R and S338F (found in single individuals), L252V (in two individuals), and A71T (in three individuals). Screening of family members of the above probands revealed a total of 19 mutation carriers, most of whom, though not all, displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…These three genes play an important role in lipid metabolism and all function as anti T2D3138394041 and a reduction of these three genes contributes to the metabolic dysfunction and its associated disorders as consequences. However, all these three genes were down-regulated upon SPION treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These three genes play an important role in lipid metabolism and all function as anti T2D3138394041 and a reduction of these three genes contributes to the metabolic dysfunction and its associated disorders as consequences. However, all these three genes were down-regulated upon SPION treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The first case report of L279 V was a heterozygous Hong Kong Chinese patient reported by Chan L et al [ 11 ]. Then, some population studies reported that the frequency of L279 V varied from 1/160 to 5/101 in Asian countries, such as Thailand, Mainland China, Taiwan and Hong Kong [ 5 , 11 , 12 , 24 27 ]. But in European continental ancestry groups, L279 V has never been reported, which may suggest that genetic variations in LPL differ between different races and ethnic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…L279 V is a disease-causing missense change with LPL deficiency only among Asian patients, probably because of the founder effect [ 5 , 24 ]. L279 V has been verified to be pathogenic by both biomedical methods and in vitro studies, such as transfecting wild-type and L279 V LPL plasmids into COS-1 cells [ 11 , 27 ]. However, there has been no in vivo research to analyze its particular pathogenic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Cys278-p.Cys283) and (p.Cys264-p.Cys275) 18,19. Multiple-species sequence alignment results showed that p.Leu279 was evolutionarily highly conserved, which indicates the significance of p.Leu279 in both the structure and function of wild-type LPL protein.Here, we also identified a heterozygous missense variant (c.553G>T; p.Gly185Cys) in APOA5 gene in the proband 1 (II-2) and his younger son (III-2).…”
mentioning
confidence: 90%